2019
DOI: 10.1200/jco.2019.37.15_suppl.506
|View full text |Cite
|
Sign up to set email alerts
|

GeparOLA: A randomized phase II trial to assess the efficacy of paclitaxel and olaparib in comparison to paclitaxel/carboplatin followed by epirubicin/cyclophosphamide as neoadjuvant chemotherapy in patients (pts) with HER2-negative early breast cancer (BC) and homologous recombination deficiency (HRD).

Abstract: 506 Background: The efficacy and toxicity of olaparib in early BC pts with homologous DNA repair deficiency (here defined as HRD score high tumors +/- germline (g) or tumor (t) BRCA mutation) is not well described. GeparOLA investigates olaparib in HER2 negative early BC with HRD. Methods: GeparOLA (NCT02789332) randomized 102 pts to either paclitaxel 80 mg/m² weekly (Pw) plus olaparib 100 mg twice daily for 12 weeks (PwO n = 65) or Pw plus carboplatin (Cb) AUC2 weekly for 12 weeks (PwCb n = 37), both followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 0 publications
0
30
0
5
Order By: Relevance
“…A confirmatory trial is currently ongoing in order to verify the benefit of single agent talazoparib (NCT02401347). GeparOLA trial (NCT02789332) is a phase II randomized trial to evaluate neoadjuvant paclitaxel and olaparib in patients with HRD [71]. The study randomized 107 patients, including 77 TNBC, to either weekly paclitaxel and daily olaparib or weekly paclitaxel and carboplatin for 12 weeks, and then followed with EC.…”
Section: Parp Inhibitors For Neoadjuvant Treatmentmentioning
confidence: 99%
“…A confirmatory trial is currently ongoing in order to verify the benefit of single agent talazoparib (NCT02401347). GeparOLA trial (NCT02789332) is a phase II randomized trial to evaluate neoadjuvant paclitaxel and olaparib in patients with HRD [71]. The study randomized 107 patients, including 77 TNBC, to either weekly paclitaxel and daily olaparib or weekly paclitaxel and carboplatin for 12 weeks, and then followed with EC.…”
Section: Parp Inhibitors For Neoadjuvant Treatmentmentioning
confidence: 99%
“…When head-to-head comparisons have been performed across different agents, data suggest that the selection for HRD can predict equally a benefit to DNA-disrupting agents, regardless of their pharmacological class. The phase II trial GeparOLA assessed the efficacy of neoadjuvant paclitaxel and olaparib vs. paclitaxel and carboplatin in patients with HRD: overall, the study failed to show a difference in terms of pCR 109 . Eventually, the combination of PARPis and carboplatin did not result in a synergistic activity, across different settings of care, providing none or narrow added clinical benefit, at the cost of increased toxicity 110,111 .…”
Section: Introductionmentioning
confidence: 99%
“…Whether the addition of PARPi to platinum‐ or nonplatinum‐based chemotherapy would further improve the treatment outcome in patients with gBRCA mutations or HR defects, is an area of active research. The recently presented GeparOLA study and BROCADE‐3 study have already shown the feasibility of this approach, with quite encouraging efficacy results. Likewise, the combination of PARPi and anti‐PD‐1/ PD‐L1 agents looks quite effective in pre‐clinical models .…”
Section: Discussionmentioning
confidence: 94%